The validity and reliability of counter movement jump height measured with the Polar Vantage V2 sports watch - Gruber, Markus; Peltonen, Jussi; Bartsch, Julia; Barzyk, Philipp (Frontiers in Sports and Active Living, 2022)
The purpose of the present study was to assess the validity and reliability of the jump height measured by the Polar Vantage V2 sports watch in comparison to a gold-standard force plate measurement. Fifteen healthy adults, seven female, age 20–42 years participated in the study and performed six sets of three CMJs, on two consecutive days. The participants wore the Polar Vantage V2 sports watch (Polar Electro Oy, Kempele, Finland) whilst performing the jumps on two force plates (AMTI, Watertown, Massachusetts, United States). Jump height was on the one hand extracted directly from the watch (“leg recovery test”) and on the other hand calculated by the flight time method with the force plate data. To assess validity, we calculated the mean absolute error, constructed Bland-Altman plots and applied an ordinary least squares regression analysis. To test for left-to-right and day-to-day reliability, we calculated Pearson and intraclass correlations. We found a mean error of ≈5% and a high correlation (r = 0.96; p < 0.001) for the jump height measured by the Polar Vantage V2 sports watch compared to the force plate measurement. The Bland-Altmann plot together with the ordinary least squares regression analysis showed no systematic bias between the methods with a minimal difference at a jump height of 30 cm. For reliability of left-to-right and day-to-day measurements, we found high Pearson and ICC correlations and no indications for systematic bias by Bland-Altmann analysis. The present study has demonstrated that the “leg recovery test” of the Polar Vantage V2 sports watch provide a valid and reliable measurement of the mean vertical jump height of three consecutive CMJs. For the first time the jump height of a CMJ can be measured solely by a sports watch without the need to attach additional sensors or measurement devices. Thus, the “leg recovery test” is an easy to administer, valid and reliable test, that can be used in future studies to measure CMJ-height in the field when lab-based assessments are unavailable or inconvenient. This opens new avenues for cross-sectional and longitudinal assessments of neuromuscular power of the lower extremities in a large number of participants.